Challenges in Linking Cognition and Survival: A Review - Rochais, Céline; Rymer, Tasmin L.; Pillay, Neville (Frontiers in Ecology and Evolution, 2022)
Linking cognitive performance with fitness outcomes, measured using both reproductive and survival metrics, of free-living animals is crucial for understanding the evolution of cognition. Although there is increasing evidence showing a link between cognitive traits and reproductive success metrics, studies specifically exploring the link between cognition and survival are scarce. We first explore which cognitive traits related to survival have been investigated in free-living animals. We also discuss the challenges associated with investigating the links between cognition and survival. We then review studies that specifically consider survival of animals of known cognitive abilities that are either free-living or in captivity and later released into the wild. We found nine studies exploring cognitive traits in wild populations. The relationships between these cognitive traits and survival were equivocal. We found a further nine studies in captive-reared populations trained to predator cues and later released into the wild. Training to recognise predator cues was correlated with increased survival in the majority of studies. Finally, different individual intrinsic characteristics (i.e., age, body condition, personality, sex) showed varied effects between studies. We argue that finding ecologically relevant cognitive traits is crucial for gaining a better understanding of how selection impacts certain cognitive traits, and how these might contribute to an individual’s survival. We also suggest possible standardized, easy to implement, cognitive tests that can be used in long-term studies, which would generate large sample sizes, take into account intrinsic characteristics, and provide an opportunity to understand the mechanisms, development and evolution of cognition.